INVESTIGATION OF EM SCATTERING BEHAVIOR OF WEAKLY INTERACTING NANOTUBES - Bespayev, Madeniyet; Iznat, Nurkeldi; Turarov, Yerassyl (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The problem of electromagnetic (EM) waves scattering by circular and arbitrary-shaped nanotubes is considered in this work. An Iso-Geometric Analysis enabled Boundary Element Method (IGABEM) is developed to estimate the scattering amount in the corresponding cases. Our research studies the scattering of EM waves caused by a nanotube and aims to optimize the shape of the nanotube so that the scattering value is maximized. The problem is of particular interest when the electrical conductivity of the nanotube is very low. This is because by only changing the shape of the nanotube, its weakly interacting (almost transparent) behavior could be altered and it would be changed into a super-scatterer of EM waves solely because of its geometry. In this work, the optimal shapes that maximize scattering were found and checked, with respect to their sensitivity, for varying wavelengths, wave angles, and distances from the source (when a point source was considered). The dependence of the scattering behavior of the nanotube on the DoFs needed for geometry representation as well as the computational accuracy as a function of the number of analysis DoFs were also examined. The best result, received by shape optimization in the context of this study, indicates that an arbitrarily shaped nanotube can scatter EM waves about 85 times higher than a circular nanotube with the same electircal conductivity and the same cross-sectional area. Such superscattering nanotubes can find applications in electromagnetic interference shielding, optical nanoantennas, biomedical imaging, spectroscopy and nanoplasmonic sensing.
Keywords: EM waves; Scattering; nanotube; Iso-Geometric Analysis enabled Boundary Element Method (IGABEM); Type of access: Embargo